Polyurethane resin composition
By adjusting the particle size ratio of polyurethane resin water dispersion and coloring agent, the problem of polyurethane resin dispersion after adding the color of the coating agent, and the optimization of high -quality membrane formation and mechanical properties.
Patent Information
- Application Number
- CN202380041262.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-30
- Filing Date
- 2023-08-10
- Publication Date
- 2025-01-28
AI Technical Summary
After adding other components such as colorants, the existing polyurethane resin aqueous dispersion has poor film-forming properties and is prone to cracks and deterioration of mechanical properties.
By adjusting the particle size ratio of polyurethane resin water dispersion and coloring agent, it is in a range below 2/3 to ensure the film formation and mechanical properties of polyurethane resin compositions.
The problem of no odor or discoloration is achieved, and no cracks occur during film formation, and the mechanical properties such as stretching strength will be optimized to form a high -quality film.
Smart Images

Figure GDA0005213214500000191 
Figure GDA0005213214500000201 
Figure GDA0005213214500000211
Abstract
Description
Technical Field
[0001] The present invention relates to a polyurethane resin composition and a laminate having a layer formed using the polyurethane resin composition. Background Art
[0002] Polyurethane resins are widely used in the manufacture of synthetic leather (including artificial leather), coating agents, adhesives, gloves, clothing, etc. due to their good mechanical strength and hand feel. Polyurethane resins are currently mainly solvent-based polyurethane resins containing N,N-dimethylformamide (DMF), but in the context of DMF restrictions in Europe, strengthening of VOC emission regulations in China, and DMF restrictions by mainstream clothing manufacturers, polyurethane resin aqueous dispersions (polyurethane dispersions) in which polyurethane resins are dispersed in water are beginning to be used for the above-mentioned purposes.
[0003] As a method for producing a polyurethane resin aqueous dispersion, a method having the following steps is known in the past: after producing a polyurethane prepolymer having an isocyanate group in a solvent such as acetone or methyl ethyl ketone, amine neutralization is performed, water is added for phase inversion emulsification, chain extension is performed, and then desolvation is performed (for example, refer to Patent Document 1). Such a conventional method uses amine as a neutralizing agent, so the odor caused by residual amine often becomes a problem. In addition, the residual amine is also considered to be the cause of polyurethane discoloration during long-term use.
[0004] Therefore, in order to solve the above-mentioned problems, a method for producing a polyurethane resin aqueous dispersion by dispersing only a nonionic component without using a neutralizing amine has been proposed (for example, refer to Patent Document 2).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-48325
[0008] Patent Document 2: Japanese Patent No. 6897883 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The production method described in the above-mentioned Patent Document 2 can solve the above-mentioned problems of odor and discoloration, and can also omit the desolvation step. In addition, the polyurethane resin aqueous dispersion obtained by the production method described in the above-mentioned Patent Document 2 can form a film with good drying properties, so that the heat energy consumption during film formation can be suppressed. The production method described in the above-mentioned Patent Document 2 can solve the problems in the production method when using amine as a neutralizing agent, and can produce a polyurethane resin aqueous dispersion with a high resin solid content.
[0011] However, the present inventors have confirmed that, in the production method described in Patent Document 2, film-forming properties can be formed without problems when the polyurethane resin aqueous dispersion is dried alone, but film-forming properties are poor when other components such as colorants including pigments are added to the polyurethane resin aqueous dispersion. When a colorant or the like is added to the polyurethane resin aqueous dispersion obtained by the production method described in Patent Document 2 to form a film, cracks are generated and mechanical properties such as tensile strength are deteriorated.
[0012] An object of the present invention is to provide a polyurethane resin composition comprising a polyurethane resin aqueous dispersion and a colorant, which can form a film without generating odor or discoloration problems, without generating cracks during film formation, and without deteriorating mechanical properties such as tensile strength.
[0013] Methods for solving problems
[0014] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that, in a polyurethane resin composition containing an aqueous polyurethane resin dispersion and a colorant, the above-mentioned problems can be solved by using a polyurethane resin composition in which the ratio of the particle size of the aqueous polyurethane resin dispersion to the particle size of the colorant is within a specific range, thereby completing the present invention having the following gist.
[0015] That is, the present invention includes the following aspects.
[0016] [1] A polyurethane resin composition comprising an aqueous polyurethane resin dispersion (A) having an oxyethylene structure and a colorant (B) comprising a pigment, wherein the ratio of the particle size (D50) at which the cumulative value is 50% in a volume frequency particle size distribution measurement of the aqueous polyurethane resin dispersion (A) to the particle size (D50) at which the cumulative value is 50% in a volume frequency particle size distribution measurement of the colorant (B), i.e., [D50 of (B) / D50 of (A)] is 2 / 3 or less.
[0017] [2] The polyurethane resin composition according to [1], wherein the polyurethane resin aqueous dispersion (A) contains a polyurethane prepolymer (a1), water (a2) and a chain extender (a3) as essential raw materials, and the polyurethane prepolymer (a1) is a reaction product of a polyol, a polyisocyanate and a compound having an oxyethylene structure and has an isocyanate group.
[0018] [3] The polyurethane resin composition according to [1] or [2], wherein the pigment is carbon black.
[0019] [4] The polyurethane resin composition according to [3], wherein the volatilization amount of the carbon black is 1% or more.
[0020] [5] The polyurethane resin composition according to any one of [1] to [4], wherein the particle size (D50) at which the cumulative value in the volume frequency particle size distribution measurement of the colorant (B) is 50% is 180 nm or less, and the particle size (D95) at which the cumulative value in the volume frequency particle size distribution measurement of the colorant (B) is 95% is 350 nm or less.
[0021] [6] The polyurethane resin composition according to any one of [1] to [5], wherein the colorant (B) further contains a polymer dispersant, and the polymer dispersant has an acid value of 30 mgKOH / g or more and an amine value of 10 mgKOH / g or less.
[0022] [7] The polyurethane resin composition according to any one of [1] to [6], wherein a film formed using the polyurethane resin composition has a ratio of breaking strength (MD direction) / breaking strength (TD direction) of less than 1.6, and a ratio of breaking elongation (MD direction) / breaking elongation (TD direction) of less than 1.2.
[0023] [8] A laminate comprising a fibrous substrate and a skin layer formed on at least one surface of the fibrous substrate from the polyurethane resin composition according to any one of [1] to [7].
[0024] [9] The laminate according to [8], further comprising a surface treatment layer made of a surface treatment agent on the surface of the skin layer.
[0025]
[10] The laminate according to [8] or [9], wherein the fibrous substrate is in a form selected from the group consisting of nonwoven fabric, knitted fabric, and woven fabric.
[0026] Effects of the Invention
[0027] According to the present invention, there is provided a polyurethane resin composition comprising a polyurethane resin aqueous dispersion and a colorant, which can form a film without causing odor or discoloration problems, cracking during film formation, or deterioration of mechanical properties such as tensile strength. DETAILED DESCRIPTION
[0028] Hereinafter, the present invention will be described in detail. It should be noted that the description of the constituent elements described below is an example for explaining the present invention, and the present invention is not limited to these contents.
[0029] (Polyurethane resin composition)
[0030] The polyurethane resin composition of the present invention contains a polyurethane resin aqueous dispersion (A) and a colorant (B).
[0031] The polyurethane resin aqueous dispersion (A) has an oxyethylene structure.
[0032] The colorant (B) contains a pigment.
[0033] The ratio of the particle size (D50) at which the cumulative value is 50% in the volume frequency particle size distribution measurement of the polyurethane resin aqueous dispersion (A) of the polyurethane resin composition of the present invention to the particle size (D50) at which the cumulative value is 50% in the volume frequency particle size distribution measurement of the colorant (B), that is, [D50 of (B) / D50 of (A)] is 2 / 3 or less.
[0034] The polyurethane resin composition of the present invention may further contain other components such as a leveling agent and a defoaming agent in addition to the polyurethane resin aqueous dispersion (A) and the colorant (B).
[0035] <Polyurethane Resin Aqueous Dispersion (A)>
[0036] The polyurethane resin aqueous dispersion (A) is an aqueous dispersion of the polyurethane resin (X). For example, the content of the polyurethane resin (X) in the aqueous dispersion is preferably in the range of 50 to 70% by mass.
[0037] The polyurethane resin (X) is a general term for polymer compounds having a urethane bond (—NHCOO—), and is generally produced by reacting a polyol with a polyisocyanate (crosslinking, curing reaction).
[0038] The polyurethane resin aqueous dispersion (A) used in the present invention has an oxyethylene structure.
[0039] The polyurethane resin aqueous dispersion (A) of the present invention preferably contains a polyurethane prepolymer (a1) having an isocyanate group, water (a2) and a chain extender (a3) as essential raw materials and is formed using these essential raw materials.
[0040] The polyurethane prepolymer (a1) is preferably a reaction product of a polyol (a1-2), a polyisocyanate (a1-3), and a compound (a1-4) having an oxyethylene structure.
[0041] In the present invention, as described above, the content of the polyurethane resin (X) is preferably in the range of 50 to 70% by mass. In this way, since the so-called solid content in the water monomer is high, the drying property of the polyurethane resin aqueous dispersion is improved, so that cracks will not be generated in the polyurethane resin film during and / or after drying, and excellent film-forming properties can be obtained. In addition, since the solid content is high, the amount of heat required for drying can be reduced. As for the content of the polyurethane resin (X), from the viewpoint of obtaining a more excellent film-forming property, it is more preferably in the range of 52 to 68% by mass, and further preferably in the range of 54 to 65% by mass.
[0042] The polyurethane resin aqueous dispersion (A) can be produced, for example, by reacting a polyol (a1-2), a polyisocyanate (a1-3) and a compound (a1-4) having an oxyethylene structure to obtain a polyurethane prepolymer (a1) having an isocyanate group, then dispersing the polyurethane prepolymer (a1) in water (a2), and then reacting a chain extender (a3) to obtain a polyurethane resin (X). It should be noted that an emulsifier may be used when dispersing the polyurethane prepolymer in water (the detailed description of the method for producing the polyurethane resin aqueous dispersion (A) is described later).
[0043] Hereinafter, each component serving as a raw material for producing the polyurethane resin aqueous dispersion (A) will be described.
[0044] <<Polyurethane prepolymer (a1)>>
[0045] <<<Polyol (a1-2)>>>
[0046] As polyol (a1-2), for example, polyether polyol, polyester polyol, polyacrylic acid polyol, polycarbonate polyol, polybutadiene polyol etc. can be used. These polyols can be used alone or in combination of two or more. It should be noted that, as polyol (a1-2), materials other than the raw materials of the compound (a1-4) with ethylene oxide structure described later are used.
[0047] The number average molecular weight of the polyol (a1-2) is preferably in the range of 500 to 100,000, more preferably in the range of 800 to 10,000, from the viewpoint of the mechanical strength of the resulting film. The number average molecular weight of the polyol (a1-2) refers to a value measured by gel permeation chromatography (GPC).
[0048] The usage ratio of the polyol (a1-2) is more preferably in the range of 40 to 90 mass %, and further preferably in the range of 50 to 80 mass %, based on the total mass of the raw materials constituting the polyurethane resin (X) in order to obtain better mechanical strength.
[0049] <<<Polyisocyanate (a1-3)>>>
[0050] As polyisocyanate (a1-3), for example, aromatic polyisocyanates such as phenylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, carbodiimidized diphenylmethane polyisocyanate, and aliphatic polyisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, dimer acid diisocyanate, norbornene diisocyanate, or alicyclic polyisocyanates can be used. These polyisocyanates can be used alone or in combination of two or more.
[0051] The usage ratio of the polyisocyanate (a1-3) is more preferably in the range of 5 to 40% by mass, and further preferably in the range of 10 to 35% by mass, based on the total mass of the raw materials constituting the polyurethane resin (X) from the viewpoint of obtaining more excellent mechanical strength.
[0052] <<<Compound having oxyethylene structure (a1-4)>>>
[0053] As the compound (a1-4) having an oxyethylene structure, for example, polyether polyols having an oxyethylene structure such as polyethylene glycol, polyoxyethylene polyoxypropylene glycol, polyoxyethylene polyoxytetramethylene glycol, and polyethylene glycol dimethyl ether can be used. These compounds can be used alone or in combination of two or more. Among them, polyethylene glycol and / or polyethylene glycol dimethyl ether are preferably used from the aspect of being able to more easily control hydrophilicity.
[0054] The number average molecular weight of the compound (a1-4) having an oxyethylene structure is preferably in the range of 200 to 10,000, more preferably in the range of 300 to 3,000, and even more preferably in the range of 300 to 2,000, from the perspective of obtaining more excellent emulsification and water dispersion stability. It should be noted that the number average molecular weight of the compound (a1-4) having an oxyethylene structure represents a value measured by gel permeation chromatography (GPC).
[0055] The proportion of the compound (a1-4) having an oxyethylene structure is preferably 5% by mass or less, more preferably 2% by mass or less, further preferably in the range of 0.25 to 2% by mass, and particularly preferably in the range of 0.5 to 1.8% by mass, based on the total mass of the raw materials constituting the polyurethane resin (X), from the perspective of obtaining more excellent emulsification, water dispersion stability and film-forming properties.
[0056] <<Water (a2)>>
[0057] As water used in the present invention, ion exchange water, distilled water, etc. can be used. These waters may be used alone or in combination of two or more.
[0058] <<Chain Extender (a3)>>
[0059] As the chain extender (a3), a chain extender having a molecular weight of less than 500 (preferably in the range of 50 to 450) can be used, and specifically, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, hexamethylene glycol, sucrose, methylene glycol, glycerol, sorbitol, bisphenol A, 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether can be used. , trimethylolpropane and other chain extenders with hydroxyl groups; ethylenediamine, 1,2-propylenediamine, 1,6-hexamethylenediamine, piperazine, 2,5-dimethylpiperazine, isophoronediamine, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-dicyclohexylmethanediamine, 3,3'-dimethyl-4,4'-dicyclohexylmethanediamine, 1,4-cyclohexanediamine, hydrazine and other chain extenders with amino groups, etc. These chain extenders can be used alone or in combination of two or more. It should be noted that the molecular weight of the chain extender (a3) represents the value calculated by the chemical formula.
[0060] As the chain extender (a3), a chain extender having an amino group (hereinafter referred to as "amine-based chain extender") is preferably used from the viewpoint that chain extension can be easily performed even at a relatively low temperature of 30° C. or less, energy consumption during the reaction can be suppressed, and further excellent mechanical strength and film-forming properties due to the introduction of urea groups can be obtained. From the viewpoint that further excellent emulsification and water dispersion stability can be obtained even when the polyurethane resin (X) is highly solidified, an amine-based chain extender having a molecular weight in the range of 30 to 250, more preferably in the range of 40 to 250, is more preferably used. It should be noted that when two or more chain extenders are used in combination, the above molecular weight represents the average value thereof, and the average value may be within the above preferred molecular weight range.
[0061] The proportion of the chain extender (a1) used is more preferably in the range of 0.1 to 30% by mass, particularly preferably in the range of 0.5 to 10% by mass, based on the total mass of the raw materials constituting the polyurethane resin (X), from the viewpoint of obtaining more excellent mechanical strength, film-forming properties, emulsification properties, and water dispersion stability, and from the viewpoint of facilitating high solid decomposition of the polyurethane resin (X).
[0062] <<Emulsifier>>
[0063] As emulsifiers that can be used when dispersing the polyurethane prepolymer in water to obtain the polyurethane resin, for example, nonionic emulsifiers such as polyoxyethylene nonylphenyl ether, polyoxyethylene lauryl ether, polyoxyethylene styrylphenyl ether, polyoxyethylene sorbitol tetraoleate, polyethylene / polypropylene copolymers, anionic emulsifiers such as fatty acid salts such as sodium oleate, alkyl sulfate ester salts, alkylbenzene sulfonates, alkyl sulfosuccinates, naphthalene sulfonates, polyoxyethylene alkyl sulfates, alkane sulfonic acid sodium salts, alkyl diphenyl ether sulfonic acid sodium salts, and cationic emulsifiers such as alkylamine salts, alkyl trimethyl ammonium salts, and alkyl dimethyl benzyl ammonium salts can be used. These emulsifiers can be used alone or in combination of two or more.
[0064] <<Method for producing polyurethane resin aqueous dispersion (A)>>
[0065] As a method for producing the polyurethane resin aqueous dispersion of the present invention, for example, the following method can be mentioned: the polyol (a1-2), the polyisocyanate (a1-3) and the compound (a1-4) having an oxyethylene group are reacted to obtain a polyurethane prepolymer (a1) having an isocyanate group (hereinafter, simply referred to as the "prepolymer step"), then the polyurethane prepolymer (a1) is dispersed in the water (a2) (hereinafter, simply referred to as the "emulsification step"), and then the chain extender (a3) is reacted to obtain a polyurethane resin (X) (hereinafter, simply referred to as the "chain extension step"), thereby producing a polyurethane resin aqueous dispersion which is an aqueous dispersion of the polyurethane resin (X).
[0066] The prepolymer process can be carried out in the absence of a solvent. In the prior art, the prepolymer process is usually carried out in an organic solvent such as methyl ethyl ketone or acetone, but a desolventizing process is required to distill off the organic solvent after the emulsification process, which requires several days of production at the actual production site. In addition, it is also difficult to completely distill off the organic solvent in the desolventizing process, and in most cases a small amount of organic solvent will remain, making it difficult to fully cope with environmental concerns. On the other hand, in the method for producing the polyurethane resin aqueous dispersion of the present invention, the prepolymer process can be carried out in the absence of a solvent, thereby obtaining a polyurethane resin aqueous dispersion that is completely free of organic solvents, and its production process can also be labor-saving.
[0067] The molar ratio [isocyanate group / hydroxyl group] of the total of the hydroxyl groups possessed by the polyol (a1-2) and the hydroxyl groups possessed by the compound (a1-4) having an oxyethylene group in the prepolymer step to the isocyanate groups possessed by the polyisocyanate (a1-3) is preferably in the range of 1.1 to 3, and more preferably in the range of 1.2 to 2, from the perspective of obtaining better film-forming properties and mechanical strength.
[0068] The reaction in the prepolymer step may be performed at 50 to 120° C. for 1 to 10 hours, for example.
[0069] The prepolymer process can be carried out by using a reactor equipped with stirring wings; a kneading machine such as a kneader, a seal ring kneader, a conical roll, a single-screw extruder, a twin-screw extruder, a triple-screw extruder, a universal mixer, a planetary mill, a main mixer, etc.; a rotary disperser such as a TK homomixer, Filmix, EbaraMilder, CLEARMIX, ULTRA-TURRAX, Cavitron, BioMixer, etc.; an ultrasonic disperser; an in-line mixer, etc., which has no moving parts and mixes by the flow of the fluid itself.
[0070] The emulsification step is preferably carried out at a temperature at which water does not evaporate, for example, a temperature in the range of 10 to 90° C. The emulsification step can be carried out using the same equipment as the prepolymer step. Among them, a kneader is preferably used from the viewpoints that the amount of oxyethylene groups introduced is small, an aqueous dispersion of a polyurethane resin having an average particle size equivalent to that of a conventional method can be stably obtained to react with a chain extender, and an aqueous dispersion of a polyurethane resin having a high content of the polyurethane resin can be easily obtained.
[0071] The chain extension step is a step of increasing the molecular weight of the polyurethane prepolymer (a1) by reacting the isocyanate group of the polyurethane prepolymer (a1) with the chain extender (a3) to obtain the polyurethane resin (X). The temperature during the chain extension step is preferably 50° C. or less from the viewpoint of productivity.
[0072] The molar ratio of the total of the isocyanate group possessed by the polyurethane prepolymer (a1) and the hydroxyl group and the amino group possessed by the chain extender (a3) [(hydroxyl group and amino group) / isocyanate group] in the chain extension step is preferably in the range of 0.8 to 1.1, and more preferably in the range of 0.9 to 1, from the viewpoint of obtaining more excellent film-forming properties and mechanical strength.
[0073] The chain extension step can be carried out using the same equipment as in the prepolymer step.
[0074] <<Characteristics of polyurethane resin aqueous dispersion (A)>>
[0075] In the present invention, a polyurethane resin composition is defined as one in which the ratio of the particle size (D50) at which the cumulative value is 50% in the volume frequency particle size distribution measurement of the polyurethane resin aqueous dispersion (A) to the particle size (D50) at which the cumulative value is 50% in the volume frequency particle size distribution measurement of the colorant (B), i.e., [D50 of (B) / D50 of (A)] is 2 / 3 or less.
[0076] When the ratio of the average particle diameter (D50) of the polyurethane resin aqueous dispersion (A) to the colorant (B) [D50 of (B) / D50 of (A)] is within the above range, the difference in particle size distribution between the polyurethane resin and the colorant can be increased, and the particle diameter of the colorant can be reduced. This is preferred because the generation of agglomerates during film formation is suppressed and cracks are less likely to occur.
[0077] D50 represents the particle size (average particle size) at which the cumulative value in volume frequency particle size distribution measurement is 50%.
[0078] Therefore, it is necessary to determine the particle size (D50) of the polyurethane resin aqueous dispersion (A) and the particle size (D50) of the colorant (B), respectively.
[0079] The particle size (D50) of the polyurethane resin aqueous dispersion (A) is determined as follows (it is noted that the measurement of the particle size (D50) of the colorant (B) will be described later).
[0080] <<<Measurement of Particle Diameter (D50) at Which Cumulative Value Is 50% in Volume Frequency Particle Size Distribution Measurement of Polyurethane Resin Aqueous Dispersion (A)>>>
[0081] Using an ultrasonic homogenizer (ULTRAHOMOGENIZER US-300E manufactured by Nippon Seiki Co., Ltd.), a substance obtained by diluting 1 g of the polyurethane resin aqueous dispersion by adding 50 g of water was pretreated at 2.5 A for 1 minute, and the particle size distribution of the pretreated substance was measured using Nanotrac WaveII manufactured by Microtrac BEL Co., Ltd. as a dynamic light scattering device.
[0082] From the viewpoint of obtaining even better film-forming properties, the particle diameter (D50) of the polyurethane resin aqueous dispersion (A) is preferably in the range of 10 to 1000 nm, more preferably in the range of 50 to 500 nm.
[0083] The molecular weight of the polyurethane resin (X) varies depending on the application and required performance, but may be appropriately selected within the range of 5,000 to 50,000, preferably 5,000 to 15,000 in terms of number average molecular weight.
[0084] <Colorant (B)>
[0085] The colorant (B) contains a pigment.
[0086] The colorant (B) is not particularly limited in form as long as it contains a pigment, and the pigment alone may be used as the colorant, or other components may be blended with the pigment.
[0087] In the present invention, the colorant (B) preferably further contains a polymeric dispersant. For example, it is more preferred that the pigment is a colorant surface-treated with a polymeric dispersant.
[0088] Examples of the pigment contained in the colorant include inorganic pigments and organic pigments.
[0089] In the present invention, carbon black is more preferably used among inorganic pigments.
[0090] Examples of inorganic pigments other than carbon black include oxides, hydroxides, sulfides, ferrocyanides, chromates, carbonates, silicates, phosphates, and metal powders.
[0091] Examples of organic pigments include nitroso pigments, dye lake pigments, azo lake pigments, insoluble azo pigments, monoazo pigments, disazo pigments, condensed azo pigments, benzimidazolone pigments, phthalocyanine pigments, anthraquinone pigments, perylene pigments, quinacridone pigments, dioxazines, isoindolines, azomethine pigments, and pyrrolopyrrole pigments.
[0092] From the viewpoint of ensuring flexibility, a pigment having a small particle size is preferred.
[0093] From the viewpoint of exerting the effects of the present invention, the pigment is preferably carbon black, and the volatilization amount of carbon black is more preferably 1% or more.
[0094] When the volatilization amount of carbon black is as high as in the above range, the amount of functional groups (OH, COOH) on the surface of carbon black is large, so that it is easy to maintain compatibility with the polyurethane resin during film formation and it is difficult to cause aggregation of particles, which is preferred.
[0095] It should be noted that the volatilization amount of carbon black refers to, for example, the volatilization (weight loss) amount when heated at 950° C. for 7 minutes, and this value can be found from product catalogs and the like.
[0096] The colorant (B) can be prepared by mixing and dispersing a pigment and a polymer-based dispersant in an aqueous medium.
[0097] The polymer dispersant is not particularly limited, and for example, a polymer pigment dispersant described in JP-A-2022-75758 can be used.
[0098] More specifically, for example, as the polymer dispersant, the polymer dispersants described below can be preferably used.
[0099] (1) A comb-shaped polymer pigment dispersant having a pigment affinity group in the main chain and / or a plurality of side chains and having a plurality of side chains constituting a solvating portion.
[0100] (2) A polymer pigment dispersant having a plurality of pigment-affinity moieties composed of pigment-affinity groups in the main chain.
[0101] (3) A linear polymer pigment dispersant having a pigment affinity portion composed of a pigment affinity group at one end of the main chain.
[0102] Here, the above-mentioned pigment affinity group refers to a functional group having a strong adsorption force on the surface of the pigment. For example, in organic sols, tertiary amine groups, quaternary ammonium groups, heterocyclic groups having basic nitrogen atoms, hydroxyl groups, and carboxyl groups can be mentioned. In hydrosols, phenyl groups, lauryl groups, stearyl groups, dodecyl groups, oleyl groups, etc. can be mentioned.
[0103] Each of the above-mentioned polymer pigment dispersants may be used alone or in combination of two or more.
[0104] Among polymeric dispersants, from the viewpoint of ensuring affinity between the pigment and the polyurethane resin (X) in the dispersion when the polyurethane resin aqueous dispersion (A) and the colorant (B) are mixed to form a coating, the polymeric dispersant preferably has a certain degree of acid value, and more preferably has an acid value of 30 mgKOH / g or more and an amine value of 10 mgKOH / g or less.
[0105] <<Characteristics of Colorant (B)>>
[0106] The particle size (D50) of the colorant (B) is determined as follows.
[0107] <<<Measurement of Particle Diameter (D50) at Which Cumulative Value Is 50% in Volume Frequency Particle Size Distribution Measurement of Colorant (B)>>>
[0108] A substance obtained by diluting 0.2 g of the colorant with 50 g of water was pretreated at 2.5 A for 1 minute using an ultrasonic homogenizer (ULTRAHOMOGENIZER US-300E manufactured by Nippon Seiki Co., Ltd.), and the particle size distribution of the pretreated substance was measured using Nanotrac Wave II manufactured by Microtrac BEL Co., Ltd. as a dynamic light scattering device.
[0109] The particle size (D50) of the colorant (B) is preferably 180 nm or less. In addition, the particle size (D95) at which the cumulative value in volume frequency particle size distribution measurement of the colorant (B) is 95% is preferably 350 nm or less.
[0110] More preferably, the particle size (D50) of the colorant (B) is 180 nm or less, and the particle size (D95) of the colorant (B) is 350 nm or less.
[0111] When the 50% particle size (D50) and the 95% particle size (D95) in the cumulative particle size distribution of the colorant (B) are within the above ranges, the particle size of the colorant can be prevented from becoming too large, and the generation of aggregates can be suppressed.
[0112] <Mixing Ratio of Polyurethane Resin Aqueous Dispersion (A) and Colorant (B)>
[0113] The amount of the colorant (B) in the polyurethane resin composition is preferably in the range of 10 to 40 parts by mass, more preferably in the range of 10 to 20 parts by mass, relative to 100 parts by mass of the resin solid content of the polyurethane resin (X) in the polyurethane resin aqueous dispersion (A). If the amount of the colorant (B) is below the above upper limit, the problem of deterioration of the coating film strength and cracks due to the increase of particles in the coating film can be effectively prevented. In addition, if the amount of the colorant (B) is above the above lower limit, the problem of deterioration of the color development and concealment of the coating film can be effectively prevented.
[0114] <Other ingredients>
[0115] The polyurethane resin composition of the present invention may contain, in addition to the polyurethane resin aqueous dispersion (A) and the colorant (B), other components such as a leveling agent, a defoaming agent, and a thickener as necessary within a range that does not impair the physical properties of the polyurethane resin obtained by curing.
[0116] As other additives, for example, emulsifiers, neutralizers, thickeners, urethanization catalysts, fillers, flame retardants, leveling agents, anti-blocking agents, film-forming aids, defoamers, foaming agents, etc. These additives may be used alone or in combination of two or more.
[0117] <Application of polyurethane resin composition>
[0118] A specific embodiment of using the polyurethane resin composition will be described.
[0119] The polyurethane resin composition of the present invention can be used as a coating agent for a fibrous substrate, for example. A coating agent is an agent for obtaining a film formed on the surface of a substrate, and includes the concept of a surface treatment agent. By coating the polyurethane resin composition on the surface of a fibrous substrate, a laminate having a layer formed of the polyurethane resin composition can be obtained.
[0120] The layer formed of the polyurethane resin composition can be formed as a skin layer on the surface of a fibrous substrate, for example. In addition, the layer formed of the polyurethane resin composition can be formed as an adhesive layer or an intermediate layer in addition to the skin layer.
[0121] A surface treatment layer using a surface treatment agent may be further formed on the surface of the layer formed of the polyurethane resin composition to obtain a laminate having a skin layer and a surface treatment layer on the surface of the fibrous substrate.
[0122] The film formed using the polyurethane resin composition does not have the problem of odor or discoloration, and does not have cracks or deterioration of mechanical properties such as tensile strength. In addition, the evaluation of mechanical properties such as breaking strength and elongation at break also shows good results. For example, the film formed using the polyurethane resin composition of the present invention has a ratio of breaking strength (MD direction) / breaking strength (TD direction) of 1.6 or less and / or a ratio of elongation at break (MD direction) / elongation at break (TD direction) of 1.2 or less.
[0123] (Laminate having layers formed using polyurethane resin composition)
[0124] The laminated body of the present invention has a layer formed using the polyurethane resin composition of the present invention.
[0125] The layer formed using the polyurethane resin composition of the present invention can be suitably used as a skin layer of a fibrous substrate. In addition to the skin layer, it can also be suitably used as an adhesive layer, an intermediate layer, or a surface-treated layer on the surface of the skin layer.
[0126] The laminate of the present invention may further have a surface-treated layer formed by a surface-treating agent on the surface of the skin layer formed using the polyurethane resin composition of the present invention.
[0127] Examples of the material of the fibrous substrate include natural fibers (plant fibers, animal fibers) such as cotton, flax, and silk; and chemical fibers such as polyester, nylon, acrylic, and polyurethane.
[0128] Examples of the form of the fibrous base material include knitted fabrics, woven fabrics, and nonwoven fabrics.
[0129] Specific examples of articles having the laminate of the present invention include synthetic leather, artificial leather, natural leather, automobile interior sheets using polyvinyl chloride (PVC) leather, sports shoes, clothing, furniture, thermoplastic olefin (TPO) leather, instrument panels, and dashboards.
[0130] The laminate of the present invention can be produced by a known dry film-forming method or a wet film-forming method. For example, the following method can be cited as an example of the dry film-forming method.
[0131] The resin composition for the skin layer is applied on the release paper with a doctor blade and then dried. Next, the resin composition for the adhesive layer is applied on the dried coating film of the skin layer with a doctor blade and then pre-dried. The nonwoven fabric is further bonded and then dried. After aging, the release paper is peeled off to obtain a laminate.
[0132] In addition, for example, as an example of the wet film-forming method, the following method can be mentioned.
[0133] After applying a polyurethane resin composition containing an organic solvent to a substrate, the substrate is immersed in water, whereby the solvent in the polyurethane resin composition is replaced with water, and the solid matter in the polyurethane resin composition is precipitated to form a film. Subsequently, the residual solvent is fully washed away with water, squeezed with a nip roll, etc., and dried to obtain a laminate.
[0134] When the laminate is produced by a wet film-forming method, a wet film-forming aid may be appropriately added to the polyurethane resin composition of the present invention in order to adjust the film-forming speed and good plane smoothness. Examples of the wet film-forming aid include castor oil, tripalmitin, silicone oil, etc. These wet film-forming aids may be used alone or in combination of two or more.
[0135] The thickness of the layer formed of the polyurethane resin composition is preferably in the range of 0.1 to 100 μm, for example.
[0136] Example
[0137] Hereinafter, the present invention will be described in further detail with reference to Examples, but the present invention is not limited to these Examples. In addition, "%" in the compositions of the following Examples means "mass %".
[0138] Information on products used in the following Examples and Comparative Examples is as follows.
[0139] (Carbon Black)
[0140] #45 (Mitsubishi Chemical, untreated carbon black, average particle size 24nm, volatile content 1.1%)
[0141] MA7 (Mitsubishi Chemical, oxidized carbon black, average particle size 24nm, volatile content 2.5%)
[0142] MA100 (Mitsubishi Chemical, oxidized carbon black, average particle size 24nm, volatile content 1.5%)
[0143] #40 (Mitsubishi Chemical, untreated carbon black, average particle size 24nm, volatile content 0.8%)
[0144] #25 (Mitsubishi Chemical, untreated carbon black, average particle size 47nm, volatile content 0.6%)
[0145] #32 (Mitsubishi Chemical, untreated carbon black, average particle size 30nm, volatile content 0.6%)
[0146] The above-mentioned volatilization amount of carbon black is a value described in the catalog. In addition, the catalog describes that the volatilization amount refers to the volatilization (weight loss) amount when heated at 950° C. for 7 minutes.
[0147] (Surfactant)
[0148] Flowlen GW-1500 (manufactured by Kyoeisha Chemical Co., Ltd., a polymer dispersant with high affinity for pigments, solid content 100%)
[0149] (Leveling agent)
[0150] BYK-348 (manufactured by BYK, polyether modified polydimethylsiloxane, non-volatile content: >90%)
[0151] (Defoaming Agent)
[0152] TEGO Foamex 800 (manufactured by EVONIK, polyether siloxane copolymer, non-volatile content 25%)
[0153] (Thickener)
[0154] Borchi Gel L75N (manufactured by Borchers, solid content 50%)
[0155] (Production Example 1)
[0156] In the presence of 0.1 parts by mass of stannous octoate, 1,000 parts by mass of a polycarbonate polyol (a material made from 1,6-hexanediol as a raw material, number average molecular weight: 2,000), 38 parts by mass of polyethylene glycol ("PEG600" manufactured by NOF Corporation, number average molecular weight: 600, hereinafter abbreviated as "PEG") and 262 parts by mass of dicyclohexylmethane diisocyanate (HMDI) were reacted at 100° C. until the NCO% reached 2.8%, thereby obtaining a polyurethane prepolymer.
[0157] The polyurethane prepolymer heated to 70° C. was stirred and mixed with 65 parts by mass of a 20% aqueous solution of sodium dodecylbenzenesulfonate ("Neogen S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an emulsifier and 948 parts by mass of water using a homomixer to obtain an emulsion. Immediately thereafter, an aqueous solution of isophorone diamine (IPDA) having an amino group content equivalent to an equimolar amount of the NCO group was added to extend the chain, and finally a polyurethane resin aqueous dispersion (A) having a polyurethane resin content of 58% by mass was obtained.
[0158] D50 of the polyurethane resin aqueous dispersion (A) is measured as follows.
[0159] Using an ultrasonic homogenizer (ULTRA HOMOGENIZER US-300E manufactured by Nippon Seiki Co., Ltd.), a substance obtained by diluting 1 g of the polyurethane resin aqueous dispersion by adding 50 g of water was pre-treated for 2.5 A for 1 minute, and the particle size distribution of the pre-treated substance was measured using Nanotrac Wave II manufactured by Microtrac BEL Co., Ltd. as a dynamic light scattering device. The results are shown in the following Tables 1-1 and 1-2.
[0160] (Production Example 2)
[0161] In a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen blowing tube, 1,000 parts by mass of a polycarbonate polyol (using 1,6-hexanediol as a raw material, number average molecular weight: 2,000), 67 parts by mass of dimethylol propionic acid, and 710 parts by mass of methyl ethyl ketone were added under a nitrogen flow, and after uniform mixing, 590 parts by mass of dicyclohexylmethane diisocyanate was added, followed by 0.1 parts by mass of stannous octoate, and the mixture was reacted at 70° C. for about 4 hours, thereby obtaining a methyl ethyl ketone solution of a polyurethane prepolymer having an isocyanate group at the molecular terminal.
[0162] Next, 51 parts by mass of triethylamine was added to the methyl ethyl ketone solution of the polyurethane prepolymer obtained by the above method, and after neutralizing the carboxyl groups in the polyurethane prepolymer, 1555 parts by mass of ion exchange water was added, and then 128 parts by mass of isophorone diamine was added to react. After the reaction was completed, methyl ethyl ketone was distilled off under reduced pressure, thereby obtaining a 35% by mass polyurethane resin aqueous dispersion (A').
[0163] D50 of the polyurethane resin aqueous dispersion (A') is measured as follows.
[0164] Using an ultrasonic homogenizer (ULTRA HOMOGENIZER US-300E manufactured by Nippon Seiki Co., Ltd.), a substance obtained by diluting 1 g of the polyurethane resin aqueous dispersion by adding 50 g of water was pre-treated for 2.5 A for 1 minute, and the particle size distribution of the pre-treated substance was measured using Nanotrac Wave II manufactured by Microtrac BEL Co., Ltd. as a dynamic light scattering device. The results are shown in the following Tables 1-1 and 1-2.
[0165] (Production Example 3)
[0166] A surfactant (12 parts by mass) was added to water (58 parts by mass), and the mixture was stirred for 5 minutes using a homodispersor. #45 (30 parts by mass) manufactured by Mitsubishi Chemical was added while stirring, and the mixture was stirred for 30 minutes. 100 g of the mixture obtained in this way and 100 g of the glass beads were placed in a 220 cc glass bottle and dispersed using a paint shaker (PAINT SHAKER manufactured by Toyo Seiki Co., Ltd.) for 120 minutes to obtain a water-based colorant (B-1).
[0167] D50 and D95 of the coloring agent (B-1) were measured as follows.
[0168] A product diluted by adding 50 g of water to 0.2 g of the colorant (B-1) was pre-treated with an ultrasonic homogenizer (ULTRA HOMOGENIZERUS-300E manufactured by Nippon Seiki Seisaku-sho) of the same apparatus as that used for the above-mentioned polyurethane resin aqueous dispersion at 2.5 A for 1 minute, and the particle size distribution of the product after the pre-treatment was measured with Nanotrac Wave II manufactured by MicrotracBEL Co., Ltd. as a dynamic light scattering apparatus. The results are shown in the following Tables 1-1 and 1-2.
[0169] (Manufacturing Examples 4 to 8)
[0170] In Production Example 3, except that each compounding component was changed as shown in the following Table 2, it carried out similarly to Production Example 3, and obtained the aqueous coloring agents (B-2) to (B6).
[0171] The D50 and D95 of the coloring agents (B-2) to (B6) were measured in the same manner as for the coloring agent (B-1). The results are shown in the following Tables 1-1 and 1-2.
[0172] (Example 1)
[0173] 100 g (100 parts by mass) of the polyurethane resin aqueous dispersion (A) was stirred with a homodispersor, and 10 g (10 parts by mass) of the aqueous colorant (B-1) was added. Next, 0.1 g of a leveling agent and 0.1 g of a defoaming agent were added, and a thickener was added so that the viscosity became about 3,000 mPa·s. Then, the mixture was stirred for 10 minutes to prepare an aqueous skin layer resin composition 1 (in the table, "aqueous skin layer resin composition" is also referred to as "aqueous skin coating").
[0174] <Coating film evaluation>
[0175] <<Coating properties>>
[0176] The aqueous skin layer resin composition 1 was applied to a release paper ("EK-100D" manufactured by LINTEC Co., Ltd.) using a knife coater to a thickness of 100 μm, and dried using a hot air dryer (70° C. × 2 minutes → 120° C. × 2 minutes). The obtained film was cut into two lengths of 100 mm and 5 mm in width in the MD direction and the TD direction to prepare a test piece.
[0177] The two ends of the test piece were clamped with chucks, and the tensile tester "Autograph AG-I" (manufactured by Shimadzu Corporation) was used to stretch the test piece at a crosshead speed of 300 mm / min (distance between markings 20 mm, initial distance between chucks 20 mm) in an atmosphere of temperature 23°C and humidity 60%, and the breaking strength and breaking elongation of the test piece were measured when the test piece broke.
[0178] <<Crack resistance>>
[0179] The aqueous skin layer resin composition 1 was applied to a release paper ("EK-100D" manufactured by Lintec Corporation) using a knife coater to a thickness of 150 μm, and dried using a hot air dryer (70° C.×2 minutes→120° C.×2 minutes) and evaluated as follows.
[0180] ○: A film was obtained after water drying, and there were no cracks in the film.
[0181] ×: The water was not dried and / or cracks were observed in the film.
[0182] <<Flexibility>>
[0183] In order to evaluate the bendability, synthetic leather to be evaluated was prepared as follows.
[0184] Preparation of adhesive layer using water-based coating
[0185] Thickener Borchi Gel 0626 (manufactured by Borchers) was added to 100 g (100 parts by mass) of HYDRAN WLA-515AR (manufactured by DIC), and the mixture was stirred with a homodispersor to a viscosity of about 6,000 mPa·s. Then, 8 g (8 parts by mass) of crosslinking agent BAYHYDUR XP2655 (manufactured by Covestro) was added and stirred for 10 minutes to prepare a water-based coating material for an adhesive layer.
[0186] Production of synthetic leather
[0187] A water-based surface layer resin composition 1 was applied to release paper ("EK-100D" manufactured by LINTEC Co., Ltd.) using a knife coater to a thickness of 150 μm, and dried using a hot air dryer (70°C × 2 minutes → 120°C × 2 minutes). A water-based coating for an adhesive layer was applied to the dried coating film using a knife coater to a thickness of 150 μm, and dried using a hot air dryer (90-100°C × 3 minutes). Then, the coated surface of the dried coating film was bonded to a nonwoven fabric using a hot roll press set at 100-130°C, thereby producing synthetic leather.
[0188] -Flexibility evaluation
[0189] The obtained synthetic leather was subjected to a bending test (-10°C, 100 times / min) using a flexometer ("Low Temperature Flexometer" manufactured by Yasuda Seiki Co., Ltd.) to measure the number of times until cracks occurred on the surface of the synthetic leather and evaluate as follows.
[0190] A: More than 30,000 times
[0191] B: more than 10,000 times, less than 30,000 times
[0192] C: Less than 10,000 times
[0193] <<Stink>>
[0194] The same synthetic leather as described in the above <<Flexibility>> column was prepared. The obtained synthetic leather was cut into a size of 200±20 cm. 2 , put it in a 1L glass beaker, heat it at 80±2℃ for 2 hours, then cool it to 60±5℃, and judge the odor according to the following criteria.
[0195] At least three judges are selected, and if the difference in the scoring results of the judges is more than one level, at least five judges are selected to conduct a retest.
[0196] If the result is level 3 or lower, it is considered that there is no problem in practical use.
[0197] Level 1: No odor
[0198] Level 2: Slight odor, but not an obstructive odor
[0199] Level 3: There is a noticeable odor, but it is not an obstructive odor
[0200] Level 4: Obstructive odor
[0201] Level 5: There is a strong obstructive odor
[0202] Level 6: Unacceptable odor
[0203] The evaluation results of the above-mentioned evaluations performed using the aqueous skin layer resin composition 1 of Example 1 are shown in the following Table 1-1.
[0204] (Examples 2-3)
[0205] In Example 1, except having changed each compounding component as shown in the following Table 1-1, it carried out similarly to Example 1, and obtained the water-based resin composition 2-3 for surface skin layer.
[0206] The aqueous skin layer resin composition was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1-1.
[0207] (Comparative Examples 1 to 6)
[0208] In Example 1, except having changed each compounding component as shown in the following Tables 1-2, it carried out similarly to Example 1, and obtained the water-based resin composition 4-9 for surface skin layer.
[0209] The aqueous skin layer resin composition was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1-2.
[0210] [Table 1-1]
[0211]
[0212] [Table 1-2]
[0213]
[0214] [Table 2]
[0215]
[0216] As shown in the examples, it is known that the polyurethane resin composition of the present invention containing a polyurethane resin aqueous dispersion and a colorant does not generate cracks when forming a coating film, can form a coating film with high strength in the MD / TD direction, and can produce synthetic leather with good bendability. In addition, the synthetic leather sheet using the polyurethane resin composition of the present invention does not have an odor (amine odor).
Claims
1. A polyurethane resin composition comprising a polyurethane resin aqueous dispersion (A) having an oxyethylene structure and a colorant (B) comprising a pigment, in, The ratio of the particle size D50 at which the cumulative value is 50% in the volume frequency particle size distribution measurement of the polyurethane resin aqueous dispersion (A) to the particle size D50 at which the cumulative value is 50% in the volume frequency particle size distribution measurement of the colorant (B), i.e., D50 of (B) / D50 of (A), is 2 / 3 or less.
2. The polyurethane resin composition according to claim 1, wherein The polyurethane resin aqueous dispersion (A) has a polyurethane prepolymer (a1), water (a2) and a chain extender (a3) as essential raw materials. The polyurethane prepolymer (a1) is a reaction product of a polyol, a polyisocyanate and a compound having an oxyethylene structure and has an isocyanate group.
3. The polyurethane resin composition according to claim 1, wherein The pigment is carbon black.
4. The polyurethane resin composition according to claim 3, wherein The volatilization amount of the carbon black is greater than 1%.
5. The polyurethane resin composition according to claim 1, wherein The colorant (B) has a particle size D50 at which the cumulative value of 50% in volume frequency particle size distribution measurement is 180 nm or less, and a particle size D95 at which the cumulative value of 95% in volume frequency particle size distribution measurement is 350 nm or less.
6. The polyurethane resin composition according to claim 1, wherein The colorant (B) further contains a polymer dispersant having an acid value of 30 mgKOH / g or more and an amine value of 10 mgKOH / g or less.
7. The polyurethane resin composition according to claim 1, wherein A film formed using the polyurethane resin composition has a ratio of MD-direction breaking strength / TD-direction breaking strength of 1.6 or less, and a ratio of MD-direction breaking elongation / TD-direction breaking elongation of 1.2 or less. 8 . A laminate comprising a fibrous substrate and a skin layer formed on at least one surface of the fibrous substrate from the polyurethane resin composition according to claim 1 .
9. The laminate according to claim 8, wherein A surface treatment layer based on a surface treatment agent is further provided on the surface of the skin layer.
10. The laminate according to claim 8, wherein The fibrous substrate is in a form selected from the group consisting of nonwoven fabric, knitted fabric, and woven fabric.
Citation Information
Patent Citations
Polyurethane resin water dispersion for inkjet ink
JP2018048325A
Water-based paint composition and multi-layer paint film
JP2022075758A